2018
DOI: 10.1080/19336918.2018.1485618
|View full text |Cite
|
Sign up to set email alerts
|

DDR1 and DDR2 in skin

Abstract: DDR1 and DDR2 are expressed in skin but their expression differs according to the skin compartment, epidermis, dermis, hypodermis and to the embryonic origin of the cells. In skin, it seems that during physiological processes such as wound healing or pathological processes such as tumorigenesis or systemic sclerosis development only one of the DDR is dysregulated. Furthermore, the altered DDR in pathological process is not necessarily the DDR implicated in basal homeostasis. Indeed, in epidermis, while DDR1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Therefore, at this junction, we cannot assert whether the inhibitory effect of DDR1‐IN‐1 in the melanoma xenografts was due to inhibition of both DDRs and a single receptor. In regard to DDR2, currently, there is a significant lack of data on the expression of DDR2 in melanoma tissues and only a few studies on the role of melanoma‐expressed DDR2 in tumor cell behavior have been published (Cario, ). Moreover, the role of tumor‐derived DDR2 in experimental metastases of melanoma cells remains unclear (Badiola et al, ; Tu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, at this junction, we cannot assert whether the inhibitory effect of DDR1‐IN‐1 in the melanoma xenografts was due to inhibition of both DDRs and a single receptor. In regard to DDR2, currently, there is a significant lack of data on the expression of DDR2 in melanoma tissues and only a few studies on the role of melanoma‐expressed DDR2 in tumor cell behavior have been published (Cario, ). Moreover, the role of tumor‐derived DDR2 in experimental metastases of melanoma cells remains unclear (Badiola et al, ; Tu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to DDR2, currently, there is a significant lack of data on the expression of DDR2 in melanoma tissues and only a few studies on the role of melanoma-expressed DDR2 in tumor cell behavior have been published (Cario, 2018). Moreover, the role of tumor-derived DDR2 in experimental metastases of melanoma cells remains unclear (Badiola et al, 2011;Tu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDR1 and DDR2 are unique among the receptor tyrosine kinases family as they represent non-integrin collagen receptors (Leitinger, 2014, Shrivastava et al, 1997, Vogel et al, 1997. Their role during embryonic development, wound healing and fibrosis is well described (Cario, 2018, Leitinger, 2014. On the contrary, their function during cancer development is less clear as they can act either as tumor-promoters or tumor-suppressors, according to the tissue of origin (Valiathan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the functional implication of DDR1 or DDR2 kinase activity in mediating sensitivity to anti-cancer therapies remains poorly defined. DDR1 and DDR2 are both expressed at different levels in skin (Cario, 2018), particularly in the epidermis from which cutaneous melanomas originate, following the malignant transformation of melanocytes (Shain development with regards to cancer cell growth and invasiveness. A recent study correlated high DDR1 expression in melanoma lesions with poor prognosis and showed that DDR1 controls melanoma cell invasion and survival in vitro and in a xenograft melanoma model (Reger de Moura et al, 2019).…”
Section: Discussionmentioning
confidence: 99%